A clay-shoveler's fracture with renal transplantation and osteoporosis: a case report - Unay Koray; Karatoprak Omer; Sener Nadir; Ozkan Korhan (Journal of Medical Case Reports, 2008)
Abstract Introduction Clay-shoveler's fracture is a rare cervicodorsal spinous process fracture and there is little information regarding the prognosis of patients with this condition in conjunction with osteoporosis and corticosteroid use. Case presentation A 39-year-old man was admitted to our institution with a 6-month history of cervicodorsal pain prior to admission. The patient had previously undergone renal transplantation and was on corticosteroids, and had developed osteoporosis. We treated him with a cervical collar, non-steroidal anti-inflammatory agents and alendronate. The patient was advised against performing weight-bearing activities for 6 months. Conclusion Clay-shoveler's fracture with osteoporosis and corticosteroid use presented by fracture of the cervicodorsal aspect of the spinous processes may be successfully treated with a collar, alendronate and long-term rest.